Persistent symptoms of severe and critical COVID-19: A cross-sectional study after more than 120 days from disease onset - Mohammed A Alraddadi; Hamad A Alyami; Nasser T Alqahtani; Noha K Khalil; Asmaa A Alraddadi; Naif H Alotaibi (Wolters Kluwer Medknow Publications, 2023)
Objective: The objective of this study is to assess the prevalence and predictors of symptom persistence associated with severe and critical coronavirus disease-2019 (COVID-19) after more than 120 days from the onset of the disease. Materials and Methods: This is a single-center, cross-sectional study of 125 adults who were admitted to King Khalid University Hospital (Riyadh, Saudi Arabia) with severe and critical COVID-19 between March 4 and December 1, 2020. Telephone interviews were conducted between April 1 and May 31, 2021, to collect data on COVID-19 symptoms persisting after more than 120 days from the onset of the disease. All of the participants had been discharged from the hospital and had resumed their normal lives. Symptoms of COVID-19 that had not been present before the onset of the disease were considered to be persistent if participants confirmed their continued presence at the time of the interview. The impact of chronic disease on persistent symptoms was considered. Results: About 42.4% (53/125) of patients had at least one or more persistent symptoms; 27.2% (34/125) had breathlessness, 5.6% (7/125) cough, and 4.8% (6/125) chest pain. These three symptoms had been present from the first presentation. Hair loss was reported by 14.4% (18/125), forgetfulness by 8% (10/125), difficulty in concentrating by 6.4% (8/125), and lack of energy by 4% (5/125). Those had manifested after more than 120 days from the symptom's onset. The major factors in suffering from persistent symptoms were intensive care unit (ICU) admission or/and fever (temperature >38°), or/and diarrhea. There was no correlation between persistent symptoms and chronic diseases. Conclusions: After more than 120 days from the confirmation of severe and critical COVID-19, more than one-third of discharged adults were found to have one or more persistent symptoms. These were mainly associated with the need for ICU admission, fever (temperature >38°), and diarrhea. More care needs to be given to COVID-19 patients in the presence of these factors and prolonged medical care would appear to be essential.